Worktime regulations and spousal labour supply - Goux, Dominique; Maurin, Eric; Petrongolo, Barbara (Bonn, 2011)
"We investigate spillovers in spousal labour supply exploiting independent variation in hours worked generated by the introduction of the shorter workweek in France in the late 1990s. We find that female and male employees treated by the shorter legal workweek reduce their weekly labour supply by about 2 hours, and do not experience any reduction in their monthly earnings. While wives of treated men do not seem to adjust their working time at either the intensive or extensive margins, husbands of treated wives respond by cutting their workweek by about half an hour to one hour, according to specifications and samples. In particular, managers and professionals respond much more strongly to the shorter legal workweek in their wives’ firms than men in lower occupations. These effects are consistent with the presence of significant cross-hour effects on labour supply for husbands, though not for wives."